CONNECTED SPEECH PATTERNS IN SPOKEN ENGLISH: A PHONOLOGICAL ANALYSIS - Ambalegin Ambalegin; Afriana Afriana (IdeBahasa, 2025)
This phonological research discusses the connected speech in spoken English. The purpose of this study is to describe the patterns of connected speech in American English and British English. The data were collected by using observation method and the technique used is note-taking. Then, the data were analyzed by using phonetic articulatory identity method. The theory used Lass’ theory related to the pronunciation corresponding to connected speech. Furthermore, the results of data analysis were presented by using descriptive narrative. The results of the study might be proposed to the important material for English Pronunciation course. The finding reveals that the connected speech processes in American English are not always the same as those in British English. The connected speech process in British English is more complicated than it in American English. However, both Englishes apply linking in terms of catenation, liaison, and gemination, elision and coalescence, and assimilation. There is a phenomenon of connected speech which is not part of any theory; [sɪŋɡɔːwɪˈtɜːn] and [ʧeɪn-j-ɛniˈmɔː].